USAHA PERPUSTAKAAN PROKLAMATOR BUNG KARNO DALAM MEREKAM SEJARAH LISAN UNTUKMELESTARIKAN PENGETAHUAN TENTANG SUKARNO (1901–1970): PENERAPAN SEJARAH LISAN DALAM MEREKAM PENGETAHUAN SOSOK MARHAEN DI BANDUNG - Aji Subekti (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2019)
The role of oral history in preserving the knowledge of Sukarno is very important to fulfil the lack of written sources. This paper is a conceptual paper and the application of recording the knowledge of Sukarno that focuses on Marhaen,as a figure, using oral  history  based  on  "Fundamentals  of Oral History Texas Preservations Guidelines". The findings showed that oral history is useful for saving and preserving knowledge about Sukarno, based on both the individual and society. Proklamator Bung Karno Library has started the oral history of Sukarno. It focused on the Marhaen as a figure. How great the name of Marhaen was until Sukarno used it as the name of an ideology. This oral history program is not easy, especially for a librarian. For that reason, one of ways that will be undertaken by the librarian is doing collaboration with other related professions, such as historians, sociologists or anthropologists. This collaboration, hopefully, can answer the difficulties. If this oral history is not conducted, the source of knowledge of Sukarno will be lost. By storing collections in the form of oral history, the librarians have given contribution to the preservation of intellectual resources.